2000
DOI: 10.1002/1521-4141(200001)30:1<204::aid-immu204>3.3.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-derived chemokine production by activated human T cells in vitro and in vivo: preferential association with the production of type 2 cytokines

Abstract: Macrophage-derived chemokine (MDC), a potent chemoattractant for chronically activated Th2 lymphocytes, is constitutively expressed by dendritic cells, B cells, macrophages, and thymic medullary epithelial cells, whereas monocytes, NK cells, and T lymphocytes produce MDC only upon appropriate stimulation. In this study, we show in vitro MDC production also by activated T cells, which preferentially associate with the production of Th2 cytokines, IL-4, IL-5, and IL-6, and inversely correlate with the production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
0
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 3 publications
(4 reference statements)
2
64
0
1
Order By: Relevance
“…This may not be surprising because JRA does have a strong type 1 component, and increases in MDC serum levels relative to healthy adults have been reported for type 2-dominated disorders such as atopic dermatitis and mycosis fungoides/Sézary syndrome but not for type 1-dominated disorders such as multiple sclerosis or Crohn's disease (31). Although only a relatively small number of samples were studied, two interesting observations are apparent.…”
Section: Discussionmentioning
confidence: 99%
“…This may not be surprising because JRA does have a strong type 1 component, and increases in MDC serum levels relative to healthy adults have been reported for type 2-dominated disorders such as atopic dermatitis and mycosis fungoides/Sézary syndrome but not for type 1-dominated disorders such as multiple sclerosis or Crohn's disease (31). Although only a relatively small number of samples were studied, two interesting observations are apparent.…”
Section: Discussionmentioning
confidence: 99%
“…Serum CCL22/MDC levels are also known to be closely related to the disease activity of atopic dermatitis [15] and mycosis fungoides/Sézary Syndrome [14], which are associated with Th2 polarization.…”
Section: Discussionmentioning
confidence: 99%
“…CCR4, the receptor of CCL22/MDC [17] and CCL17/TARC [18], is primarily Activated Th2 cells produce CCL22/MDC [14], IL-4, and IL-13. IL-4 and IL-13 are able to amplify CCL22/MDC production from Th2 cells [13] and monocytes [19].…”
Section: Discussionmentioning
confidence: 99%
“…It is probable that, as for basophils, TH2-type mRNA ϩ cells may be recruited in vivo through additional chemokine receptors, such as CCR4 and CCR8, expressed on the latter cells (Bonecchi et al, 1998). In this context, it has been reported that in human allergic cutaneous reactions, there is an overexpression of thymus activation regulated chemokine (CCL17) (Kakinuma et al, 2001;Vestergaard et al, 2000) and macrophage-derived chemokine (CCL22) (Galli et al, 2000), which bind CCR4 (Imai et al, 1997(Imai et al, , 1998. The in vivo relevance of the CCR4 pathway on TH2 cell recruitment in allergic inflammation has been assessed indirectly using antibody against macrophage-derived chemokine in a murine model, where it was mainly effective on the chronic recruitment of TH2 cells (Lloyd et al, 2000).…”
Section: Sénéchal Et Almentioning
confidence: 99%